Climate wars : the flight for survival as the world overheats - Dyer, Gwynne (Oxford, 2011)
Dwindling resources, massive population shifts, natural disasters, spreading epidemics, drought, rising sea levels, plummeting agricultural yields, crashing economies, political extremism - these are just some of the expected consequences of runaway climate change in the decades ahead - and any of them could tip the world towards conflict. Bold, unflinching, and based on exhaustive research, "Climate Wars" grippingly reveals how world leaders are likely to react, and promises to be one of the most important books of the coming years.
Keywords: Climate change